2022
DOI: 10.3390/en15197185
|View full text |Cite
|
Sign up to set email alerts
|

Research on Collaborative Design of Performance-Refined Zero Energy Building: A Case Study

Abstract: Building Information Modeling (BIM), as an auxiliary design platform, is increasingly adopted in construction projects. However, it is not widely applied in the collaborative design of zero energy buildings (ZEBs), due to the cross-discipline and complex features of ZEB projects and lack of research on the procedure and method of collaborative design in this field. This paper introduces a BIM-based collaborative design method for ZEBs. From the perspective of the technical requirements of ZEBs, the study elabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…While previous research has identified barriers to PD implementation, there is limited empirical evidence on how overcoming these barriers can lead to successful sustainable building outcomes [40,41]. This lack of literature hinders our understanding of the factors that contribute to a project's sustainability success [42,43]. To bridge this gap, this study aims to provide empirical proof of the relationship between overcoming obstacles to PD implementation and achieving sustainable building goals.…”
Section: The Association Concerning Pd Implementation On Project Sust...mentioning
confidence: 99%
See 1 more Smart Citation
“…While previous research has identified barriers to PD implementation, there is limited empirical evidence on how overcoming these barriers can lead to successful sustainable building outcomes [40,41]. This lack of literature hinders our understanding of the factors that contribute to a project's sustainability success [42,43]. To bridge this gap, this study aims to provide empirical proof of the relationship between overcoming obstacles to PD implementation and achieving sustainable building goals.…”
Section: The Association Concerning Pd Implementation On Project Sust...mentioning
confidence: 99%
“…Path coefficients must be determined and quantified for this purpose. Therefore, we constructed a causal chain between £, PD adoption hurdles, and references [43,44]. Therefore, the linear equation may be used to describe the found structural connection as an internal relationship between the £, µ, and €1 rule in the operational model.…”
Section: Functioning Modelmentioning
confidence: 99%
“…Nowadays, various software systems have been widely used, and the theory of cooperative design has been deeply explored [4] . So far, numerous developers, such as Shenzhen Sifang Zhiyuan, Beijing Lizheng Software, Beijing Yuanxinke, Weiheng Haojian, have already created cooperative design platforms [5] . However, due to their neglect of the actual situation of design institutes, many cooperative design software is limited by modes and resisted by designers, and thus fail to be promoted [6] .…”
Section: The Current Situation Of Collaborative Management Systemmentioning
confidence: 99%
“…(3) Academic papers on the competition [65][66][67]. The building design of SDC2021 was limited to a 20 * 20 m area.…”
Section: Data Sourcesmentioning
confidence: 99%